Simultaneous RP-HPLC determination of sparfloxacin and dexamethasone in pharmaceutical formulations (Brazilian Journal of Pharmaceutical Sciences, 2013)
The present study describes the development and subsequent validation of simple and accurate stability indicating RP-HPLC method for the determination of sparfloxacin and dexamethasone in pharmaceutical formulations in the presence of their stress-induced degradation products. Both the drugs and their stress-induced degradation products were separated within 10 minutes using C8 column and mixture of methanol and 0.02 M phosphate buffer pH 3.0 (60:40 v/v, respectively) as mobile phase at 270 nm using diode array detector. Regression analysis showed linearity in the range of 15-105 µg/mL for sparfloxacin and 5-35 µg/mL for dexamethasone. All the analytes were adequately resolved with acceptable tailing. Peak purity of the two drugs was also greater than 0.9999, showing no co-elution peaks. The developed method was applied for simultaneous determination of sparfloxacin and dexamethasone in pharmaceutical formulations for stability studies.